CURRENT TRENDS IN SURGICAL TREATMENT OF VOCAL FOLD POLYPS: A MINI-REVIEW - Čukić, Professor Ognjen; Arsović, Nenad; Jovanović, Milan (Medicinski podmladak, 2023)
Vocal fold polyps represent one of the most common benign organic disorders affecting the larynx in the general population, and a relatively frequent cause of long-standing hoarseness. The exact etiology is unclear, but poor vocal behavior has been suggested as the principal etiologic factor. Histopathologically they are characterized by various structural alterations in the vocal fold superficial lamina propria, and typical clinical finding is of a solitary, unilateral and well-defined vocal fold lesion. Vocal fold polyps usually require surgical removal using microlaryngoscopy with cold steel excision in general anesthesia, which has been the practice standard for the last 60 years. Microlaryngoscopy offers the surgeon an unparalleled magnified view of the vocal folds and very precise work on a still operative field without a specific time limit. The introduction and technological development of ambulatory endoscopy and various laser systems provided the surgeon with ample therapeutic opportunities, including operating some of the patients in the office setting in local anesthesia. These outpatient procedures are technically simple and cost-effective, require fewer medical personnel, exclude general anesthesia-related risks, and are less time-consuming both for the patient and the physician. Nevertheless, we feel the contemporary laryngologist should be able to perform both conventional microlaryngoscopy and office-based surgery for vocal fold polyps, depending on the clinical situation.